Selection of Pyramided Barley Advanced Lines for Stripe Rust, Leaf Rust and Crown Rust Diseases Using Molecular Markers - Amgai, Resham B.; Pokharel, Shreejan; Pantha, Sumitra; Parajuli, Atit; Subedi, Sudeep; Dhital, Shambhu P. (Nepal Journal of Biotechnology, 2020)
Barley diseases are the major yield limiting factors for barley cultivation in Nepal. Stripe/Yellow rust (P. striformis f.sp. hordei and P. striformis f.sp. tritici), leaf rust (Puccinia hordei), and crown rust (P. coronata) are the major rust diseases in Nepal. Pyramiding resistance genes against all these rust diseases are possible through molecular marker assisted breeding. Sweden originated barley variety ‘Bonus’ is found resistant to stripe rust and having linked microsatellite markers for stripe rust and crown rust resistance. Similarly, Nepalese hull-less barley variety ‘Solu Uwa’ and Nepalese awn-less barley landrace NPGR Acc# 2478 have linked microsatellite markers for leaf rust resistance. Therefore, one polymorphic sequence tagged sites (STS) marker (ABG054) for stripe rust resistance, two polymorphic simple sequence repeats (SSR) markers (Bmac0144h and HVM049) for leaf rust and one polymorphic SSR marker (Bmag0006) for crown rust resistance were used to select the advanced barley lines (at F8 stage) from above parents. Field screening of stripe rust resistance was also conducted. Among 51 advanced and field disease resistance lines from Bonus/Solu Uwa cross, we have selected 10 pyramided lines for all three types of barley rust resistance. Similarly, among 39 advanced and field disease resistance lines from Bonus/NPGR Acc#2478 cross we have selected three pyramided lines and advanced for further yield testing for general cultivation purpose. The chances of losing the desired gene are high in late generation selection using molecular marker assisted selection (MAS); but the chances of getting agronomically superior varietal output will also increase.